HIV Prevalence and Correlations in Prisons in Different Regions of the World: A Review Article - Golrokhi, Raheleh (Open AIDS J, 2018)
The prevalence of HIV is substantially higher among prisoners than the general population, while the incidence varies considerably in different regions around the world. If we consider Sub-Saharan Africa as one region with the highest prevalence of HIV, data on African prisoners would be limited. Despite the low prevalence of HIV in the Middle East and North Africa, its incidence is rising in these regions with a few exceptions; there are insufficient data on HIV prevalence in prisons. A similar situation is present in both Pacific and Central Asia as well as in Eastern Europe. A high rate of infection is mainly observed among prisoners in Western and Central parts of Europe, since the data from these are more available than other parts. Nowadays, the sexual transmission mode and tattooing are important ways in HIV risks among prisoners after injecting drug use as the most common route of HIV transmission in all regions. However, it is difficult to compare and analyze the prevalence of HIV among prisoners in different regions regarding the limited data and different methods which they used in collecting data. Eventually, it can certainly be said that prisons are one of the high-risk places for HIV transmission; on the other hand, can be a suitable place for implementing HIV case-finding, linkage to treatment and harm reduction programs.